2022
DOI: 10.1002/gps.5728
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological approach to subjective cognitive complaints in cognitively unimpaired older people: A systematic review

Abstract: Objective: A systemized approach to subjective cognitive complaints (SCCs) in elderly people is needed owing to the high prevalence of such complaints and their impact on the psychosocial well-being of those affected. The aim of this study was to carry out a systematic review of the characteristics and effectiveness of intervention programmes that use a neuropsychological approach to target SCCs in cognitively unimpaired older people and that are tested in randomized controlled trials. Methods:The search inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(220 reference statements)
0
1
0
Order By: Relevance
“…It is clearly demonstrated that CS helps to counteract age-related cognitive decline [ 29 ], which could have implications for public health policies focused on promoting healthy cognitive ageing and design of prevention and intervention programmes for older adults with subjective memory complaints [ 30 ]. However, more studies need to be conducted on people with SMC to detail the effects of these interventions [ 29 , 31 ] in preventing future progression to dementia [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is clearly demonstrated that CS helps to counteract age-related cognitive decline [ 29 ], which could have implications for public health policies focused on promoting healthy cognitive ageing and design of prevention and intervention programmes for older adults with subjective memory complaints [ 30 ]. However, more studies need to be conducted on people with SMC to detail the effects of these interventions [ 29 , 31 ] in preventing future progression to dementia [ 32 ].…”
Section: Introductionmentioning
confidence: 99%